What is an image? - Elkins, James, 1955-; Naef, Maja, 1973- (Stone art theory institutes (Series) ;, 2011)
"Brings together historians, philosophers, critics, postcolonial theorists, and curators to ask how images, pictures, and paintings are conceptualized. Issues discussed include concepts such as "image" and "picture" in and outside the West; semiotics; whether images are products of discourse; religious meanings; and the ethics of viewing"--Provided by publisher.